The effect of rosemary ointment on the grade I pressure ulcers in ICU patients: A randomized clinical trial - Fatemeh Khoshoei Parizi (Tehran University of Medical Sciences, 2021)
Background & Aim: Pressure ulcers have been identified as one of the most important and challenging issues in patient’s well-being. Based on the evidence, rosemary extract compounds can affect wound healing. The aim of this study was to determine the effect of rosemary ointment on pressure ulcer healing in patients admitted to the Intensive Care Unit. Methods & Materials: In this single-blind randomized parallel clinical trial, 70 patients who met the inclusion criteria were selected purposefully and assigned to the groups by stratified randomization method. In the intervention group, rosemary ointment was applied once a day for seven days. The control group received routine care. Data were collected using the Pressure Ulcer Scale for Healing (PUSH) before the intervention and on the third and seventh days after the intervention. Data were analyzed using independent t-test, chi-square test, and two-way repeated measurements ANOVA with SPSS 18 software. Results: The mean scores of PUSH decreased significantly in the intervention group while remained unchanged in the control group (P=0.001) one week after the intervention. The effect of time and interaction effect was also significant (P=0.001). Comparison of the ratio of complete ulcer healing in the two groups showed a significant difference between the two groups (p=0.004). Conclusion: Rosemary ointment facilitated healing and prevented the progression of grade І pressure ulcers in the Intensive Care Unit. Therefore, the use of this ointment, as a low-risk, uncomplicated, available, and inexpensive intervention, is recommended in such patients.